Methodological conception with a multidisciplinary approach for educational exclusion and inclusion in vocational training - Santana-Borrego, Osvaldo Pedro (2021)
The study on socio-educational exclusion and inclusion is an urgent issue for the contemporary academic world as a process that demands, due to its social imprint, of a methodological conception with a multidisciplinary approach for professional training in Cuban higher education. The article gathers some hypotheses on the improvement of the NUC in view of the mchallenges it faces due to the socio-cultural conditions that occur in the country for the construction of a prosperous and sustainable society. In this sense, the topic tries to highlight dissimilar assessments on the creation, innovation and transfer of scientific knowledge, which allow facing the socio-educational change and promoting the scientific progress of the country immersed in an increasingly convulsive scenario generated byneoliberal globalization and the set of actions that are articulated in the Conceptualization of the Economic and Social Model of Cuban socialist development.